DEVELOPMENT OF pH-DEPENDENT CHRONOMODULATED DELIVERY SYSTEMS OF 5-FLUOROURACIL AND OXALIPLATIN TO TREAT COLON CANCER - B. H., JASWANTH GOWDA; SHANKAR, S. J.; MUNISAMY, MURALI; R. S., AKSHATHA; SAGAR, V. S. (International Journal of Applied Pharmaceutics, 2020)
Objective: To develop two different oral formulations such as 5-fluorouracil (5-FU) tablets and oxaliplatin (OX) microspheres which were further filled into capsules and coated with pH-sensitive polymer (eudragit S-100) for the chronotherapeutic treatment of colon cancer (Fluorouracil: Oxaliplatin regimen) to perform as a substitute for intravenous (IV) route based chronomodulated chemotherapy. Methods: The 5-FU tablet formulation was prepared with alginate and guar gum polymers in varied concentrations using wet granulation technique in two varieties such as granules coated and tablet coated formulations using eudragit RSPO as coating material to achieve controlled drug release. Alongside OX microspheres were formulated using the ionotropic gelation methodology in combination with alginate and chitosan polymers in varying concentrations to accomplish a time-controlled drug release. Prepared formulations were evaluated for pre-compression and post-compression parameters, percentage yield, percentage drug entrapment, Fourier transformed infrared spectroscopy (FT-IR), Differential scanning calorimetry (DSC), Scanning electron microscopy (SEM), In vitro and Ex vivo dissolution studies. Results: Pre-compression and post-compression parameters for 5-FU tablets were satisfied with Indian pharmacopeia specifications. The entrapment efficiency of OX microspheres were increased due to the elevated concentration of polymers up to a certain level as seen in A7M, further greater the concentration of polymer resulted in a decline of entrapment efficiency as seen in A4M and A8M. The optimized formulations A14T and A14M were shown in vitro drug release of 90.36 % by 24 h and 79.63 % by 9 h respectively. Conclusion: The two different oral formulations of 5-FU (Tablets) and OX (Microspheres) were found to be successful in controlled drug release. Therefore they can be efficiently used to control the rate of drug release to the colon in synchronization with the circadian timing system in the belief of improved therapeutic efficacy, tolerability and overall survival rate of cancer patients. Hence it is promised to be a better alternative for intravenous route based chronomodulated chemotherapy.